Democratic politics and voting behaviour in Ghana. (December 2015) - Adams, Samuel; Agomor, Kingsley S.
What determines the vote choice in Ghana? This paper examines this question using a data set on voting behaviour generated from a nationwide survey of 2042 voters from the ten regions of Ghana based on six national elections held between 1992 and 2012. The results based on descriptive analyses and logistic regressions indicate that political parties tackle substantive issues during African elections, but generally voice them through valence appeals rather than by staking out distinct positions. Further, the results show that campaign message and the ethnicity of the presidential candidate matter in the vote choice. It is worth noting, however, that of the seventeen factors identified by respondents as most important, ethnicity ranked only 14th. This finding suggests that the declarative information of respondents is not consistent with their real intentions. Overall, the findings of the study show that both patronage politics and programmatic policies matter in winning elections. Accordingly, politicians need to focus on enhancing the credentials they bring to the political arena and improve their image in terms of how best they are able to achieve the public good.